Exploring the Literature on Bixa Orellana L. for its Therapeutic Potential: A Review - Ms. Pallavi Maruti Patil; Dr. Vanita G. Kanase (International Journal of Pharma and Bio Sciences, 2021)
Bixa orellana L. an Indian medicinal plant which belongs to the family Bixaceae referred to as “urucum,” has been utilized by indigenous communities in Brazil and alternative tropical countries for many biological applications, that indicates its potential use as a vigorous ingredient in pharmaceutical products. It is an ayurvedic herb used since ancient times for medication which enlightened the importance of the leaves of Bixa orellana to possess significant medicinal value. Bixa orellana L. popularly recognised as annatto plant is known for reddish orange dye annatto that’s created in plant structure portion of its seeds, that is one amongst the foremost necessary food grade natural colourant wide employed in dairy trade, confectionary and bakery products. Annatto, which contains the antioxidant bixin, is employed in food, cosmetic, and textile industries as a natural colorant.. The phytochemical screening supported the protocols within the literature, showed the presence of bioactive metabolites such as polyphenols, alkaloids, saponins, tannins, steroids, anthraquinones, sterols, terpenes and reducing sugars. Published research studies in in-vitro and in-vivo techniques indicate that various extracts of Bixa leaves exhibit antioxidant, anti-inflammatory, analgesic, broad antimicrobial, hypoglycemic and antidiarrheal activities. The previous art review of the phytoconstituents shows that B. orellana contains a large form of biologically active compounds like bixin, norbixin, β-carotene, lutein, tocotrienol, tocopherols, sesquiterpenes, monoterpenes, etc. The literature broadcast well-characterized information on the origin, phytoconstituents and cosmeceutical uses of B. orellana from scientific literature aspects in a quite scattered way. The present review compiles up-to-date information that reveals the recent findings on its cultivation and distribution, potential medicinal applications with its Pharmacological and safety aspects.